Multiple ligand binding sites regulate the Hedgehog signal transducer Smoothened in vertebrates - Byrne, E; Luchetti, G; Rohatgi, R; Siebold, C (Elsevier, 2017)
The Hedgehog (Hh) pathway plays a central role in the development of multicellular organisms, guiding cell differentiation, proliferation and survival. While many components of the vertebrate pathway were discovered two decades ago, the mechanism by which the Hh signal is transmitted across the plasma membrane remains mysterious. This fundamental task in signalling is carried out by Smoothened (SMO), a human oncoprotein and validated cancer drug target that is a member of the G-protein coupled receptor protein family. Recent structural and functional studies have advanced our mechanistic understanding of SMO activation, revealing its unique regulation by two separable but allosterically-linked ligand-binding sites. Unexpectedly, these studies have nominated cellular cholesterol as having an instructive role in SMO signalling.